2003
DOI: 10.1097/01.inf.0000069765.43405.3b
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bronchiolitis-associated deaths among infants in the United States

Abstract: VLBW and LBW infants are at increased risk of dying with bronchiolitis, even when taking into account other risk factors. Although infants weighing <2500 g at birth are at increased risk for dying with bronchiolitis, the majority of bronchiolitis deaths occur among infants of normal birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 41 publications
7
88
0
9
Order By: Relevance
“…Furthermore, many studies included a large number of premature infants, a condition that is closely related with low birthweight, thus hampering independent evaluation of this factor. Some recent studies have found that low birthweight independently increases the risk of hospitalization due to RSV infection [11,20,21] and the risk of RSV-associated death [3,15]. Our results reinforce the observation that low birthweight should be considered as an underlying condition that increases the severity of RSV-related illness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, many studies included a large number of premature infants, a condition that is closely related with low birthweight, thus hampering independent evaluation of this factor. Some recent studies have found that low birthweight independently increases the risk of hospitalization due to RSV infection [11,20,21] and the risk of RSV-associated death [3,15]. Our results reinforce the observation that low birthweight should be considered as an underlying condition that increases the severity of RSV-related illness.…”
Section: Discussionsupporting
confidence: 89%
“…Both factors are associated with low socio-economic status, a factor that we have not been able to investigate, but which has been related to a greater risk of severe RSV infections [1,2]. Recently, young maternal age has been independently associated with a higher risk of bronchiolitis-associated deaths in the United States [15]. Interestingly, 5 % of the infants hospitalized in that study belonged to the gypsy ethnic group, a proportion higher than that in our population, which, lacking official statistics, we estimate is lower than 1 % [16].…”
Section: Discussionmentioning
confidence: 99%
“…15 Use of palivizumab was generally consistent with the AAP guidelines at the time of enrollment 15,16 and published literature on potential risk factors for RSV morbidity, such as prematurity and child-care attendance, 8 and low birth weight (LBW; <2500 g). 22,23 Based on cumulative data, approximately 90% of infants were premature, 83% had LBW and 47% were enrolled in child-care or were exposed to another child in the household who attended child care. The definition of child-care attendance was left to the discretion of each site.…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction can lead to atelectasis, which can further worsen breathing and respiratory function. Epidemiological studies 4 have shown that bronchiolitis infection is associated with a high degree of morbidity but low mortality.…”
Section: Definition and Pathophysiologymentioning
confidence: 99%